SOSIALIASI PENERAPAN RESTORATIVE JUSTICE BAGI PELAKU TINDAK PIDANA - Abdillah, Muhammad Rasyid; Pardede, Rudi; Anita, Rizqa (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Proper knowledge and understanding of the handling of criminal acts based on restorative justice play an important role in the implementation of restorative justice activities in police institutions by investigators and assistant investigators. This service aims to increase the knowledge and understanding of investigators and support investigators regarding the handling of criminal acts based on restorative justice. In particular, this service conducts training on the mechanisms for implementing restorative justice by investigators and assistant investigators at police institutions. From the results of the posttest, it can be seen that there has been an increase in the knowledge and skills of investigators and assistant investigators regarding the handling of criminal acts based on restorative justice based on the Chief of Police Regulation No. 8 (2021).